Advances in Web-Based Learning - ICWL 2016 15th International Conference, Rome, Italy, October 26-29, 2016, Proceedings - Chiu, Dickson K.W.; Marenzi, Ivana; Nanni, Umberto; Spaniol, Marc.; Temperini, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the refereed proceedings of the 15th International Conference on Web-Based Learning, ICWL 2016, held in Rome, Italy, in October 2016. The 19 revised full papers presented together with 10 short papers and 4 poster papers were carefully reviewed and selected from 110 submissions. The papers are organized in topical sections on design for learning; education and teaching; massive open online courses; mobile learning; modeling for learning; serious games; social-collaborative learning; and support for learning.
Design for learning -- Education and teaching -- Massive open online courses -- Mobile learning -- Modeling for learning -- Serious games -- Social-collaborative learning -- Support for learning.
Keywords: Computer science; Computer communication systems; Computers; Artificial intelligence; Pattern recognition; Education -- Data processing; Computer Science; Computers and Education; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Computer Communication Networks